Growth and yield of maize applicated by Rizhobium spp. from legume and non-legume rhizosphere - Widodo, Tirto Wahyu; Muhklisin, Ilham; Nugroho, Setyo Andi; Wardana, Rudi; Ummah, Umi Safitri Alifia (Future Science, 2023)
Rhizobium spp can affect plant growth in non-legume crops directly by synthesis of phytostimulator and solubilization of inorganic phosphate. However, the ability of Rhizobium spp from legume and non-legume rhizosphere to trigger the growth of non-legume crops is different. This research aims to analyze the ability of Rhizobium spp isolates to produce IAA hormones and phosphate solvent and determine the response of maize with the application of Rhizobum spp from the legume and non-legume rhizosphere. This study was carried out in two stages, where the first stage at Bioscience Laboratory Politeknik Negeri Jember, while the second stage at Kaliurang field, Jember, Indonesia (altitude 146 m asl, temperature 21°C - 34°C, and soil type was incepstisol) from September 2022 to January 2023. The field experiment was arranged in a complete randomized design (crd) with the application of Rhizobium spp isolates from various rhizosphere as a treatment consisting of without Rhizobium spp (control), maize-rhizosphere isolate, rice-rhizosphere isolate, soybean-rhizosphere isolate, edamame-rhizosphere isolate, and peanut-rhizosphere isolate. Every treatment was replicated four times. The results showed that Rhizobium spp isolates from legume and non-legume rhizospheres can synthesize indole acetic acid and solubilize phosphate. This condition was indicated by the solubilized phosphate content in the planting medium, which was higher in the application of Rhizobium spp compared to the control. Inoculation of Rhizobium spp from several rhizospheres showed a significant effect on plant height, stem diameter, ear weight without husks, and ear dry weight compared to control. These bacteria are able to trigger the growth of maize through direct and indirect mechanisms. In addition, the plant height that was treated with maize-rhizosphere Rhizobium spp was better than rice. It is suspected that Rhizobium spp from the maize rhizosphere is more adaptable when applied to growing media for maize crops, so that it can increase plant height.